Organizational behavior - Hellriegel, Don.; Slocum, John W.; Woodman, Richard W. (Cincinnati, Ohio : South-Western College, 2001)
This book is divided into three parts: Individual Processes; Group and Interpersonal Processes; and Organizational Processes.
Keywords: Organization; Organizational behavior